Peran dan Strategi Human Capital dalam Meningkatkan Produktivitas Karyawan di Industri - Meisya Amanda; Deswita Maheswari; Azahra Aura; Rifda Anas; Rony Edward Utama (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to explore the role and strategy of human capital in improving employee productivity within Indonesia’s banking industry. Amid digital transformation, efficiency demands, and increasingly competitive financial markets, human resource management must evolve from merely administrative functions into a strategic pillar. Using a descriptive qualitative approach, data were collected through semi-structured interviews and document analysis across several banking institutions. The findings indicate that human capital strategies involving competency development, digital-based training, talent mapping, and adaptive leadership have a positive impact on employee performance. Adaptive and collaborative leadership styles also emerge as a key factor in supporting these strategies. However, challenges such as resistance to change and digital readiness remain present. This research provides practical implications for the development of human capital policies that are more adaptive, human-centered, and sustainable in the banking sector.